Pulmonary Hypertension in a Patient With Kartagener’s Syndrome and a Novel Homozygous Nonsense Mutation in CCDC40 Gene: A Case Report - Dai, Hai-Long; Wang, Duolao; Guang, Xue-Feng; Zhang, Wei-Hua (Frontiers in Medicine, 2022)
Kartagener’s syndrome is a subgroup of primary ciliary dyskinesia (PCD), a genetically heterogeneous condition characterised by sinusitis, bronchiectasis, and situs in versus. Genetic testing has importance for their diagnosis. Here, we report a chinese patient with Kartagener’s syndrome. Transthoracic echocardiography showed severely elevated right ventricular systolic pressure. Right heart catheterisation demonstrated a pre-capillary pulmonary hypertension. Whole-exome sequencing indicated that she had a novel homozygous nonsense mutation, c.2845C > T, p.Gln949*, in exon 18 of CCDC40 and a heterozygotic mutation, c.73G > A, p.Ala25Thr, in exon 1 of DNAH11. She was diagnosed as Kartagener’s syndrome with pulmonary hypertension. Her symptoms improved significantly by treatment of antibiotics, expectorant drugs, bronchodilators, and oxygen therapy treatment. Our findings extend the mutation spectrum of CCDC40 gene related Kartagener’s syndrome, which is very important for gene diagnosis of the disease.